Comprehensive bibliometric analysis of sirtuins: Focus on sirt1 and kidney disease - Liu, Tongtong; Mu, Shujuan; Yang, Liping; Mao, Huimin; Ma, Fang; Wang, Yuyang; Zhan, Yongli (Frontiers in Pharmacology, 2022)
Sirtuins, as regulators of metabolism and energy, have been found to play an important role in health and disease. Sirt1, the most widely studied member of the sirtuin family, can ameliorate oxidative stress, immune inflammation, autophagy, and mitochondrial homeostasis by deacetylating regulatory histone and nonhistone proteins. Notably, sirt1 has gradually gained attention in kidney disease research. Therefore, an evaluation of the overall distribution of publications concerning sirt1 based on bibliometric analysis methods to understand the thematic evolution and emerging research trends is necessary to discover topics with potential implications for kidney disease research. We conducted a bibliometric analysis of publications derived from the Web of Science Core Collection and found that publications concerning sirt1 have grown dramatically over the past two decades, especially in the past five years. Among these, the proportion of publications regarding kidney diseases have increased annually. China and the United States are major contributors to the study of sirt1, and Japanese researchers have made important contributions to the study of sirt1 in kidney disease. Obesity, and Alzheimer’s disease are hotspots diseases for the study of sirt1, while diabetic nephropathy is regarded as a research hotspot in the study of sirt1 in kidney disease. NAD+, oxidative stress, and p53 are the focus of the sirt1 research field. Autophagy and NLRP3 inflammasome are emerging research trends have gradually attracted the interest of scholars in sirt1, as well as in kidney disease. Notably, we also identified several potential research topics that may link sirt1 and kidney disease, which require further study, including immune function, metabolic reprogramming, and fecal microbiota.